2008
DOI: 10.2109/jcersj2.116.915
|View full text |Cite
|
Sign up to set email alerts
|

Compositional dependence of properties of SnO-P2O5 glasses

Abstract: Binary SnO-P2O5 (SP) glasses with 52-72 SnO mol% were examined. Glass transition temperature, density, refractive index and absorption edge were studied for transparent SP glasses. The structure of SP glasses was evaluated by FT/IR and Raman spectroscopy. The water durability was investigated by weight loss and Raman spectroscopy for SP glass samples immersed in distilled water at 30-70°C. Raman spectra indicated in the immersion test that Q 1 units form and Q 2 units decrease as a result of water attack upon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
43
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 20 publications
6
43
0
3
Order By: Relevance
“…(100 ¹ x)P 2 O 5 glasses tends to decrease with increasing SnO content, 8) meaning that the force constant of SnO bonds is much smaller than that of PO bonds. Indeed, as reported by Cha et al 8) and Lim et al, 9) the intensity of the bands at the low frequency side in xSnO. (100 ¹ x)P 2 O 5 glasses increases with increasing SnO content.…”
Section: ¹1mentioning
confidence: 99%
“…(100 ¹ x)P 2 O 5 glasses tends to decrease with increasing SnO content, 8) meaning that the force constant of SnO bonds is much smaller than that of PO bonds. Indeed, as reported by Cha et al 8) and Lim et al, 9) the intensity of the bands at the low frequency side in xSnO. (100 ¹ x)P 2 O 5 glasses increases with increasing SnO content.…”
Section: ¹1mentioning
confidence: 99%
“…Here, on this change of the phosphate network, no particular difference between SnO and MnO were identified from the Raman spectra, thus implying their similar structural roles. It is known that Sn resides in general as an Sn 2+ state, and that the Sn-O-P bonds replace the P-O-P bonds in a SnO-P 2 O 5 binary system [8,29]. Zotov et al [22] also reported that Mn can be in its 2+, 3+ or 4+ state, resulting in a coordination number of 5.7 ± 0.4 within the metaphosphate glass, which indicates mixed coordination states between 4 and 6.…”
Section: Ps Glass Pm Glassmentioning
confidence: 99%
“…For example, their low softening temperature allows them to be used to develop Pb-free sealing materials based on phosphate glasses [6,7]. Some phosphate glasses containing BaO, CaO, SnO or ZnO have been proposed as replacements for the Pb-rich glasses that show a low glass transition temperature and a high thermal expansion coefficient [8][9][10][11]. On the other hand, phosphate glasses incorporating transition metal oxides are known to be semiconducting, which promises potential applications as electrical materials [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With phosphate addition, the glass cullet might experimentally approach a phosphosilicate glass system. We then exploited the chemical behavior of phosphate in the silicate network matrix, i.e., its high ionic field strength [12] to attract the rare-earth element, its tendency to form discrete anion complexes [13,14] to cluster the rare-earth element away from the silicate, and its low durability [15,16] to leach phosphate with rare-earth element using water. To study the effect of phosphate addition on rare-earth element, photoluminescence spectroscopy can be employed to record the emission spectra of the element, especially in glass samples lacking transparency.…”
Section: Introductionmentioning
confidence: 99%